1997
DOI: 10.1136/ard.56.10.596
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests and high resolution computed tomography of the lungs in patients with rheumatoid arthritis

Abstract: Results-A significant decrease of FEV1/ FVC, FEF25%, FEF50%, FEF75%, FEF25-75%, and TLCO was observed (p<0.05) and 13.2% of the patients had a small airways involvement defined by a decrease of FEF25-75% below 1.64 SD. The most frequent HRCT findings were: bronchiectasis (30.5%), pulmonary nodules (28%), and air trapping (25%). The patients with small airways involvement had a high frequency of recurrent bronchitis (75% v 34%, p=0.05) and bronchiectasis (71% v 23%, p=0.019). The patients with bronchiectasis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1
22

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 21 publications
8
92
1
22
Order By: Relevance
“…These findings do not contradict the claim that rheumatoid lung disease occurs more frequently in patients with longstanding RA 2 . A high prevalence of airway abnormalities was also observed in several previous HRCT studies on patient populations with relatively long mean disease durations [3][4][5] .…”
Section: Drs Mori and Cho Replysupporting
confidence: 49%
“…These findings do not contradict the claim that rheumatoid lung disease occurs more frequently in patients with longstanding RA 2 . A high prevalence of airway abnormalities was also observed in several previous HRCT studies on patient populations with relatively long mean disease durations [3][4][5] .…”
Section: Drs Mori and Cho Replysupporting
confidence: 49%
“…The erythrocyte sedimentation rate tends to be higher in those with BR, but there were no other significant differences between the 2 groups, either hematologically or serologically. [14][15][16] Demoruelle et al postulated a link between autoimmunity in RA and airway damage. These authors studied 3 groups of patients: subjects without inflammatory arthritis but with elevated anti-cyclic citrullinated peptide (CCP) antibodies, antibodies-negative controls, and subjects with early seropositive RA.…”
Section: Etiologymentioning
confidence: 99%
“…Modern studies have found symptomatic bronchiectasis with a prevalence of 2.7% in RA subjects, compared to 0.03% in the general population 2 . High resolution computed tomography (HRCT) studies demonstrate the prevalence to be much higher, with radiological BR in RA populations repeatedly reported in the region of 30% [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%